2020
DOI: 10.1186/s12944-020-01366-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of CYP19A1 and CYP1A2 genetic polymorphisms with type 2 diabetes mellitus risk in the Chinese Han population

Abstract: Background: Type 2 diabetes mellitus (T2DM), one of the global health issues, is a group of metabolic diseases and is affected by several genetic loci in the clinical phenotype. This study intended to ascertain associations between CYP19A1 and CYP1A2 gene polymorphisms with the T2DM risk in Chinese Han. Methods: Seven single nucleotide polymorphisms (SNPs) in total including five of CYP19A1 (rs4646, rs6493487, rs1062033, rs17601876 and rs3751599) and two of CYP1A2 (rs762551 and rs2470890) from 512 T2DM patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…As we have said, vitamin D performs multiple functions in our body and is involved in many diseases. Most of the actions performed by vitamin D are related to its intake and the affinity of its precursors with the vitamin D nuclear receptor (VDR) [ 27 , 28 ]. The VDR is expressed in organs, such as the gut, skeleton, and parathyroid gland in the ovaries and testicles; above all, the function of vitamin D at the level of both sexes is poorly understood [ 27 , 28 ].…”
Section: The Relationship Between Vitamin D and Estrogensmentioning
confidence: 99%
See 3 more Smart Citations
“…As we have said, vitamin D performs multiple functions in our body and is involved in many diseases. Most of the actions performed by vitamin D are related to its intake and the affinity of its precursors with the vitamin D nuclear receptor (VDR) [ 27 , 28 ]. The VDR is expressed in organs, such as the gut, skeleton, and parathyroid gland in the ovaries and testicles; above all, the function of vitamin D at the level of both sexes is poorly understood [ 27 , 28 ].…”
Section: The Relationship Between Vitamin D and Estrogensmentioning
confidence: 99%
“…Most of the actions performed by vitamin D are related to its intake and the affinity of its precursors with the vitamin D nuclear receptor (VDR) [ 27 , 28 ]. The VDR is expressed in organs, such as the gut, skeleton, and parathyroid gland in the ovaries and testicles; above all, the function of vitamin D at the level of both sexes is poorly understood [ 27 , 28 ]. It has been observed that vitamin D and estrogen have a double relationship in the sense that low levels of estrogen are associated with falls of osteopenia or rickets, while it has been seen that VDR at the level gonadal plays a role in the production of estrogen [ 27 , 28 ].…”
Section: The Relationship Between Vitamin D and Estrogensmentioning
confidence: 99%
See 2 more Smart Citations
“…90 Yang et al found that CYP19A1 upregulation promotes oestrogen production, attenuates IR via the transcription factor forkhead box o 1 (Foxo1), and inhibits lipid accumulation in the liver. 91 Evangelos et al reported that in an insulin resistant state, CYP7B1 stimulation leads to the advancement of steatohepatitis from simple steatohepatitis. 92 CYP4A and CYP4F play important roles in hepatic fatty acid metabolism.…”
mentioning
confidence: 99%